2019
DOI: 10.1111/ijd.14589
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic features of lichen planopilaris in Northern Iran: a prospective observational study

Abstract: Background Dermoscopy can be helpful in assessing nonpigmented lesions and inflammatory processes like lichen planopilaris (LPP). Material & Methods In this observational prospective study, 81 patients with a cicatricial alopecic patch on their scalp were included and underwent dermatologic examination. A biopsy was taken from the active part of the lesion based on dermoscopy evaluation. Results Analysis of 44 patients with definite diagnosis of LPP revealed that the mean age at the time of presentation was 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…A total of 22 studies (15 original studies, 7 case reports) reported on trichoscopic features of lichen planopilaris. The analyzed group consisted of 356 patients [4,17,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Vessels.…”
Section: Lichen Planopilarismentioning
confidence: 99%
“…A total of 22 studies (15 original studies, 7 case reports) reported on trichoscopic features of lichen planopilaris. The analyzed group consisted of 356 patients [4,17,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Vessels.…”
Section: Lichen Planopilarismentioning
confidence: 99%
“…Pili torti is identified in 31.82-51.9% of patients with lichen planopilaris [89,111]. It is usually present in long-lasting disease [89,111].…”
Section: Pili Torti Associated With Cicatricial Alopeciasmentioning
confidence: 99%
“…Pili torti is identified in 31.82-51.9% of patients with lichen planopilaris [89,111]. It is usually present in long-lasting disease [89,111]. Other characteristic trichoscopic features of lichen planopilaris are perifollicular scaling and perifollicular erythema [112].…”
Section: Pili Torti Associated With Cicatricial Alopeciasmentioning
confidence: 99%
“…[3][4][5] Dermatoscopy allows doctors to better assess the superficial structure of the epidermis and dermis by attaching the camera to a magnifying glass. 6 Similarly, RCM can afford observation of the three-dimensional section of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…But it does not achieve good sensitivity for inspecting deep skin structures and cytomorphological details. 6 In contrast to dermatoscopy, RCM allows further information regarding the tissue and cell morphology from the superficial layers of the skin down to the superficial reticular dermis. 7 However, at the aspect of observing structures of superficial skin lesions, RCM is not as intuitive as dermatoscopy.…”
Section: Introductionmentioning
confidence: 99%